2005
DOI: 10.1002/polb.20679
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of elastomeric blends by atomic force microscopy

Abstract: The bulk mechanical properties of a blend of elastomers are found to depend on the micro and nano scale morphology of the phases of the materials in the blend. In this study, we examine the phase morphology of blends of incompatible elastomers using Atomic Force Microscopy (AFM). Specifically, nanoindentation and Tapping Mode AFM (TMAFM) imaging techniques are used as experimental tools for mapping the composition of unfilled elastomeric blends. Depending on the composition of the blend, either co-continuous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Image build from "phase signal" data is usually called as "material contrast" image. Phase imaging is commonly used to show material contrast in polymer blends and composites [10]. This method is very precise and it allows to detect the structures in composite materials in a nanometer range.…”
Section: Afm Imaging Of Pla/polyacrylate Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Image build from "phase signal" data is usually called as "material contrast" image. Phase imaging is commonly used to show material contrast in polymer blends and composites [10]. This method is very precise and it allows to detect the structures in composite materials in a nanometer range.…”
Section: Afm Imaging Of Pla/polyacrylate Compositesmentioning
confidence: 99%
“…These properties determine the polymer behavior in the processes of adhesion, adsorption, permeation, catalysis, friction, wetting, printing etc. Among various experimental techniques allowing the characterization of the surface properties, the significance of AFM systematically increases [8][9][10]. Nowadays, AFM plays a key role in microelectronics, nano-and biotechnologies.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the blend morphology became co-contiuous when the NR loading increased to 50%. Achalla et al [39] examined the phase morphology of the unfilled NR/ BIIR blends using Atomic Force Microscopy (AFM), they found that NR is the dispersed phase when BIIR content is larger than 50 wt%. In addition, a co-continuous morphology was observed for a 50/50 NR/ BIIR blend.…”
Section: 2mentioning
confidence: 99%
“…[15] The study of blends containing latex has grown considerably in the search for specific properties. [16][17][18][19] Systematic research contributions using natural latex have been published [20][21][22][23][24] combining spectroscopy and microscopy, [15] morphology and electrical potential, [16] colloids and films. [17] Rubber is a substance with glass transition temperature (T g ) below room temperature, composed by long flexible chains, which are arbitrarily agglomerated and entangled.…”
Section: Introductionmentioning
confidence: 99%